2015
DOI: 10.1016/j.jegh.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported sleep duration and sleep habits in type 2 diabetes patients in South Trinidad

Abstract: The present study aims to determine the prevalence of self-reported sleep duration and sleep habits and their associated factors in patients with type 2 diabetes in Trinidad. This was a cross-sectional multicenter study. There were 291 patients with type 2 diabetes studied. Sleep habits were assessed using the Epworth Sleepiness Scale (ESS) and the National Health and Nutrition Examination Survey sleep disorder questionnaire. Demographic, anthropometric and biochemical data were also collected. The sample had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
4
31
2
Order By: Relevance
“…This study revealed a high prevalence of poor sleep quality among T2DM patients (55.6%) than non-diabetes (controls) (32.3%). This is in agreement with studies conducted in USA (55%) [20], Korea (49%) [21], Kenya (53.4%) [8], and Trinidad and Tobago, (63.9%) [22]. However, this finding is higher than the finding of another similar study in Iran (38%) [9].…”
Section: Discussionsupporting
confidence: 91%
“…This study revealed a high prevalence of poor sleep quality among T2DM patients (55.6%) than non-diabetes (controls) (32.3%). This is in agreement with studies conducted in USA (55%) [20], Korea (49%) [21], Kenya (53.4%) [8], and Trinidad and Tobago, (63.9%) [22]. However, this finding is higher than the finding of another similar study in Iran (38%) [9].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, women, older adults, and those with poor glycemic control had poorer sleep quality, consistent with previous findings. 7,30,31 These findings further support the construct validity of the adapted PSQI. The use of a global score of PSQI has inherent clinical significance.…”
Section: Discussionsupporting
confidence: 67%
“…People with poor sanitation have a high risk for water-borne diseases and worm infestation [ 23 , 39 ]. Likewise, poor, irregular, and short sleep is associated with metabolic disease, obesity, type 2 diabetes, hypertension, and cardiovascular disease, mostly in women [ 40 , 41 ], which coincides with our findings.…”
Section: Discussionsupporting
confidence: 91%